Driving of strong nightside reconnection and geomagnetic activity by polar cap flows: Application to CME shocks and possibly other situations. (October 2018) - Lyons, L.R.; Gallardo-Lacourt, B.; Zou, Y.; Nishimura, Y.; Anderson, P.; Angelopoulos, V.; Donovan, E.F.; Ruohoniemi, J.M.; Mitchell, E.; Paxton, L.J.; Nishitani, N.
Abstract: Previous studies have shown that dynamic pressure impacts (e.g., shocks initiating CME storms) with southward IMF promptly lead to strong auroral nightside activity and concurrent poleward expansion (indicating strong nightside reconnection), and strong enhancements in convection and currents. Here we use a combination of ground-based ASI and radar observations to further describe this response, to address what is driving the strong activity, and to suggest similar driving in other situations. Consistent with some previous studies, we find that shock driven auroral activity and poleward expansion resembles a substorm, but starts from an already broad MLT sector without much subsequent azimuthal expansion and without classical brightening of the equatorward-most arc. We furthermore find a large enhancement of meso-scale ionospheric polar cap flows heading towards the nightside separatrix immediately after shock impact. Recent studies have shown that such enhanced flows often cross the separatrix leading to plasma sheet flow bursts, poleward boundary intensifications (PBIs), streamers, and poleward motion of the polar cap boundary from reconnection. Thus these flow enhancements, which must extend outward along field lines from the ionosphere, are an attractive candidate as the driver for the almost immediate strong auroral, current, and reconnection activity resulting from shock impact. We also discuss and present some evidence that this phenomenon may be more general, leading to similar oval responses without a shock impact, including during and following the expansion phase of some substorms. These suggestions could lead to some possibly fundamental questions, such as when do polar cap convection enhancements lead to a substorm growth phase versus leading directly to strong polar expansion of, and strong activity along, the auroral oval field line region? Highlights: Immediate strong auroral, current, reconnection activity results from shock impact. Shock driven aurora resembles substorm expansion; broader, from poleward boundary. Enhanced meso-scale polar cap flows towards nightside separatrix after shock impact. Above enhanced flows attractive candidate for driver of immediate strong responses.